Effect of inhibition of glutathione synthesis on insulin action: in vivo and in vitro studies using buthionine sulfoximine - KHAMAISI, Mogher; KAVEL, Oren; ROSENSTOCK, Moti; PORAT, Michal; YULI, Michal; KAISER, Nurit; RUDICH, Assaf (Biochemical journal, 2000)
Decreased cellular GSH content is a common finding in experimental and human diabetes, in which increased oxidative stress appears to occur. Oxidative stress has been suggested to play a causative role in the development of impaired insulin action on adipose tissue and skeletal muscle. In this study we undertook to investigate the potential of GSH depletion to induce insulin resistance, by utilizing the GSH synthesis inhibitor, L-buthionine-[S,R]-sulfoximine (BSO). GSH depletion (20-80% in various tissues), was achieved in vivo by treating rats for 20 days with BSO, and in vitro (80%) by treating 3T3-L1 adipocytes with BSO for 18 h. No demonstrable change in the GSH/GSSG ratio was observed following BSO treatment. GSH depletion was progressively associated with abnormal glucose tolerance test, which could not be attributed to impaired insulin secretion. Skeletal muscle insulin responsiveness was unaffected by GSH depletion, based on normal glucose response to exogenous insulin, 2-deoxyglucose uptake measurements in isolated soleus muscle, and on normal skeletal muscle expression of GLUT4 protein. Adipocyte insulin responsiveness in vitro was assessed in 3T3-L1 adipocytes, which displayed decreased insulin-stimulated tyrosine phosphorylation of insulin-receptor-substrate proteins and of the insulin receptor, but exaggerated protein kinase B phosphorylation. However, insulin-stimulated glucose uptake was unaffected by GSH depletion. In accordance, normal adipose tissue insulin sensitivity was observed in BSO-treated rats in vivo, as demonstrated by normal inhibition of circulating non-esterified fatty acid levels by endogenous insulin secretion. In conclusion, GSH depletion by BSO results in impaired glucose tolerance, but preserved adipocyte and skeletal muscle insulin responsiveness. This suggests that alternative oxidation-borne factors mediate the induction of peripheral insulin resistance by oxidative stress.